Enhanced performance of graphene-oxide Polyethersulfone Nanocomposite membrane wastewater and its fouling mechanism - Nik Abdul Ghani, Nik Rashida; Jami, Mohammed Saedi; Hasnain Isa, Mohamed (2021)
Membrane fouling is still a great challenge in filtration process for wastewater treatment which limits its technical and economic performance. To prevent and control on fouling it is important to understand the filtration behaviour and fouling mechanism. In this study, a new graphene oxide-polyethersulfone nanocomposite (GPN) membrane is fabricated and later the performance and rejection of heavy metals removal were studied using a dead-end filtration system. The performance of the fabricated GPN membrane was measured by evaluating pure water flux, salt and heavy metals removal. Fouling mechanisms are investigated for lead-containing wastewater using pore blocking models. From the results, cake filtration was found to dominate all other filtration mechanisms with the highest R2 at all the applied transmembrane pressure. Furthermore, the experimental results confirmed that adding GO to the membrane improved pure water flux, and heavy metals removal, and can be used as a novel method for preparing high performance membranes in wastewater treatment.